Nigeria at work : a survey of the psychology of work among Nigerians - Olugbile, Femi.; Guaranty Trust Bank (Nigeria) (Ikeja, Lagos State, Nigeria : Malthouse Press, 1997)
Runs through the field of sociology of work, and beyond, exploring practical details of field work and finer points of the theory of work.
Includes index.
oif 11/02/15
Loan
Keywords: Work ethic -- Nigeria; Working class -- Nigeria -- Attitudes; Public opinion -- Nigeria; Nigeria -- Economic conditions -- 1970- -- Public opinion